Stakeholder perspectives on skills required for health technology developers: a qualitative study in Thailand - Phaisawang, Sranya; Na Nakorn, Thanyaphong; Trivijitsilp, Prasert; Srikiatkhachorn, Anan (Frontiers in Digital Health, 2025)
BackgroundThroughout history, medical education has developed in response to societal changes and advances in biological research and technology. Health technology, encompassing devices, medicines, vaccines, and digital health systems, is transforming healthcare with increased effectiveness and efficiency. Thailand, a popular medical tourism destination, intends to shift its focus to high-quality healthcare services and advanced technologies for long-term economic sustainability. This study identifies necessary skills for health technology developers to help create a technology-driven healthcare ecosystem and prepare human capital in the field.MethodsIn this qualitative study, in-depth interviews with diverse stakeholders in health and health technology industries were conducted to investigate the role of health technology in future healthcare and the skills required for health technology developers. Qualitative Content Analysis was carried out. Participants included national health policy makers, university presidents, hospital directors, and health technology company administrators. The study utilized the electronic Delphi method for ranking skills through multiple interview rounds, ensuring thorough evaluation of significant topics.ResultsThis study involved interviews with sixteen stakeholders in health technology, focusing on its importance and impact on future healthcare. Participants discussed three major areas of technology: molecular technologies, biomedical engineering technologies, and health information technologies. Delocalization, personalization, and digitalization are key components of healthcare transformation. The challenges and skills needed for health technology developers were categorized into four domains including, Health Science, Health Technology, Product Development & Design and Marketing & Entrepreneurship.ConclusionOur study revealed the significance of technology in healthcare transformation. We identified four skill categories that health technology developers must possess. (1) Health Science, (2) Health Technology, (3) Product Development & Design, and (4) Marketing & Entrepreneurship were among these domains. A systematic strategy for developing these skills is a crucial success factor in human capital preparation for future technology-driven healthcare.